Estudo do polimorfismo genético de espécies do gênero Aniba (Lauraceae) utilizando marcadores ISSRs - Benzaquem, Denise Corrêa (2009)
The Lauraceae family is known to have species of great economic importance, either by its your wood or for its your use in cooking, in folk medicine, among others. The use of aromatical herbs with pharmacological properties is quite widespread, because of known effects like antifungal activity, insect repellent, antiinflammatory, anticholynesterase activities, analgesic, among others, is found in volatile oils. The genus Aniba is one that stands out by having more aromatic species of high commercial value, however much of its species has been falsely marketed by the difficulty of their identification. In this work, inter Simple Sequence repeats (ISSR) markers were used to assess the genetic variability end phylogeny of A. rosaeodora, A. canelilla end A. parviflora. Vegetative tissues of 57 accessions were obtained from two locations in Reserva florestal Adolfo Lisboa Ducke in Manaus and Maués. They are tested 30 aleatory primers and selected seven, that generated 321 amplified fragments, from those 227 showed polymorphism (86.29%). The number of observed alleles and index Shannon ranged from 1.3271 to 1.450 and 0.0931 to 0.0805 respectively. Cluster analyses (UPGMA) were performed from ISSR date set. The results illustrate the genetic relationship among the three species of the genus Aniba. The smallest genetic distance of 0.1041 was found between populations of A. roseadora and A. parviflora. Therefore, the species A. roseadora and A. parviflora present a greater degree of genetic relationship. These results add new information regarding the genetic diversity in species of the genus Aniba, thus contributing towards the biological knowledge of this species, and providing with subsides for future breeding and conservation program.